Language Play in the Aramaic Letters from Hermopolis - Wesselius, Jan-Wim (Aramaic studies, 2006)
The scribe of the Aramaic family correspondence of the fifth century BCE, which was found in Hermopolis in Egypt in 1945, as a kind of language play deliberately presented the same information in these letters in different words, in effect creating parallelisms between the letters and sometimes even within individual letters. In some cases, this observation helps us to find new interpretations of difficult passages in the Hermopolis letters. Such language play is, albeit in different forms, very common in ancient West Semitic texts, both when dealing with mundane and with highly important political and religious subjects.